Implementation of SDGs on Decent Work and Economic Growth Indicators in Palu City - Vini Alviani Safitri Sepang; Edhi Taqwa; Patta Tope; Suparman Suparman; Failur Rahman (Transpublika Publisher, 2025)
Palu City's recovery after a disaster encounters obstacles in reaching SDG 8 because of restricted availability of good job opportunities, uneven access to training for jobs, and poor collaboration among stakeholders. This calls for using evidence to pinpoint policy focuses and key players. This study aims to analyze the priority criteria and roles of stakeholders in creating decent work and supporting economic growth in Palu City by referring to the 8th Sustainable Development Goals (SDGs) indicator. The approach used is the Analytic Hierarchy Process (AHP) method, which allows systematic decision-making through pairwise comparisons. Data were obtained through questionnaires distributed to nine respondents representing the government sector, private sector, NGOs, and universities. The results showed that the Job Training criterion was the main priority with the highest weight of 0.562, followed by Investment (0.242), Labor Intensive (0.123), and Creative Industry (0.071). In terms of actors, the Private Sector occupies a dominant position with a total weight of 0.8425, indicating a significant role in supporting the creation of decent work. This study emphasizes the importance of collaboration between the private sector and the government, as well as the need to increase the contribution of NGOs and universities in supporting training, innovation, and empowerment of local communities.